Development of tilt table with visual feedback function for hemiplegia patients - Cho, J.; Choi, J.; Nam, T.; Park, J.; Park-Ko, I.; Ibrahim, F. (2007)
Due to damaged vertebrae nerves, serious disease and aging, patients who have to lie down for long period of time need to exercise to maintain up-right standing position and recover their muscle power of paralytic leg. This study describes the development of an intelligent tilt table which can provide a patient with visual feedback of exercise to increase the effect of rehabilitation. This could be possible by measuring and displaying the knee bent angle and pressure for each foot during exercise in real time. It is expected that patient's exercising effect can increase by self-monitoring these two values during exercise.